Unexamined Zen: Challenges from Dōgen’s Zen Buddhism - Dunlap, Rika (Journal of Chinese philosophy, 2023)
The traditional narrative of Zen Buddhism focuses on a religious experience that goes beyond words and concepts. I argue that Dōgen’s understanding of enlightenment is not limited to a religious experience, as it involves a creative process of Buddha-making that demands the flexibility to present a novel expression of the Buddha way with the transiency of the impermanent world. In arguing for the processual understanding of the Buddha way and enlightenment, I refer to the fluidity of dao in Chinese philosophy to shed light upon the significance of creativity in authentic practice. By doing so, I explain why an unexamined Zen is problematic for Dōgen.